1988
DOI: 10.1093/eurheartj/9.suppl_m.37
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of training in coronary patients: a critical review of the literature

Abstract: Past studies have claimed that vigorous exercise programmes have positive effects on postinfarction patients' mental health. Results of controlled studies suggest that a significant antidepressant effect of exercise on postinfarction patients has not been shown reliably. The evidence also suggests that in the long run neither anxiety and pain threshold nor social anxiety are reduced by physical exertion. Furthermore, sustained exercise may cause some psychological harm, and it seems that adherence to exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Findings are less conclusive regarding the relationship between exercise and depression scores among nondepressed individuals (Lennox, Bestell, & Stone, 1990;Raglin, 1990). The only well-controlled, randomassignment, and prospective design studies to examine the psychosocial effects of exercise among MI survivors found no consistent beneficial effects (Erdman & Duivenvoorden, 1983;Greenland & Chu, 1988;Langosch, 1988;Stem & Clearly, 1982). Greenland and Chu (1988) argued that among MI survivors it is more likely that mood disturbance affects exercise performance than that exercise performance affects mood.…”
Section: Discussionmentioning
confidence: 99%
“…Findings are less conclusive regarding the relationship between exercise and depression scores among nondepressed individuals (Lennox, Bestell, & Stone, 1990;Raglin, 1990). The only well-controlled, randomassignment, and prospective design studies to examine the psychosocial effects of exercise among MI survivors found no consistent beneficial effects (Erdman & Duivenvoorden, 1983;Greenland & Chu, 1988;Langosch, 1988;Stem & Clearly, 1982). Greenland and Chu (1988) argued that among MI survivors it is more likely that mood disturbance affects exercise performance than that exercise performance affects mood.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies of rehabilitation that have used appropriate measures and control groups have shown rather little benefit for exercise rehabilitation [10][11][12][13], They have also show'n that the majority of patients re cover very well without any special form of extra care. Our own evaluation of standard care, extra counselling exercise classes and a battery of specific measures found few dif ferences between the three groups [ 10], How ever, patients were more satisfied with exer cise and counselled patients described longer working time and greater frequency of sex eighteen months later.…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…In coronary patients, emotional disturbances in the sense of increased anxiety and depression are often documented (Blodgett & Pekarik, 1987;Mayou e t a/., 1978a, h ;Wishnie, Hackett & Cassem, 1971). General reviews of studies on effects of exercise on anxiety and depression in clinical populations (Fletcher e t al., 1992;Hughes, 1984;Langosch, 1988) emphasize inconclusive results.…”
mentioning
confidence: 99%